Adaptivity in the inclusive transition to school - Then, Daniel; Pohlmann-Rother, Sanna (Frontiers in Education, 2024)
The transition to school is a key juncture in an individual's educational trajectory, with far-reaching effects on the development of children and their families. Successful transitions require flexibility in the design of the transition process, addressing the needs of the persons involved in an adaptive manner. Adaptivity is also considered crucial for the success of inclusive transitions. However, a systematic breakdown of the aspects that characterize the concept of adaptivity in the context of inclusive school entry is not available at this point. This article therefore provides a conceptualization of adaptivity in the inclusive transition to school as well as a review of the current literature focusing this topic. The goal is to develop a model that structures the various aspects of adaptivity at school entry and offers an overview of the way these aspects are important to design the transition successfully according to current findings of empirical research. Building on a concept of transitions informed by ecological systems theory, we are guided by the assumption that adaptivity at transition to school may occur in three forms: as a feature of the persons involved in the transition; as a feature of the processes that moderate the course of the transition; and as a feature of the structures that frame the transition. Based on this distinction, we develop a model that presents adaptivity in the inclusive transition to school.